STUDY OF THE CHANGE PA (Polyethylene) NET YARN IMMERSION IN SEA WATER AND FRESH WATER - Rika Fina Armita; Isnaniah Isnaniah; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
ABSTRACT This research was conducted in April 5 to May 15, 2017in Laboratory of Fishing Gear Material of Aquatic Resources Faculty of Fisheries and Marine University of Riau, Pekanbaru. The purpose of this research is to know how long the fishing gear of PE (Polyethylene) net yarn can be used in the waters. The method used in this research is the experimental method, the result data for changes of the length net yarn is processed using the formula according with SNI 08-0889-1989 and then analyzed by using T-test. From the results of research undertaken according to SNI 08-0889-1989 that the PE threads changed the length of the net yarn after soaking in sea water and fresh water. Long change of net yarn soaked in seawater and fresh water changes on day 40 and day 50, while the net threads of unhesitized PE do not change the length of the net yarn on the 10th day until the 50th day. Meanwhile, if seen from statistical analysis by using T test comparison of PE threads soaked in sea water and fresh water on the 10th day until the 30th day has the value of Ho accepted because there is no difference in yarn length change, whereas on day 40 and day The 50th Ho is rejected due to differences in the length of the yarn change. Keywords: Changes Of Net Yarn, Sea Waters, Fresh Water.